White theology in dialogue with Black Theology: Exploring the contribution of Klippies Kritzinger - Wyngaard, George J.van (HTS teologiese studies, 2016)
This article explores the contribution of South African missiologist and theologian Klippies Kritzinger to a critical and anti-racist white theology. It analyses his academic work in response to Black Consciousness and Black Theology from publications during his doctoral studies, throughout the transition to democracy and into the present, where this theme remains a constant presence in his work. The article explores his use of liberation, conversation and re-evangelisation in constructing a white response to Black Theology and a suggested ministry to the white community. In analysing his contribution various models of contextual theology, in particular that of Steven Bevans, are used in order to position Kritzinger and illuminate Kritzinger’s approach. Bevans’ praxis, counter-cultural and translation models are used to emphasize different aspects of Kritzinger’s theology for liberating whiteness.Keywords: Whiteness; Klippies Kritzinger; anti-racism